Plant diveristy of Al-Khoms – Misrata Province in Libya - Makhlouf, Mohammed (The Libyan Journal of Science, 2022)
The present parer concernes mainly with the plant species diversity of Al- Khoms - Misrata province. The survey of plant species of such area was taken in between 2018-2020. A total number of 375 different plants have been collected representing 62 families, 241 genera, and 375 species, of which 51 families and 307 species are belonging to dicotyledons, 8 families and 65 species belonging to monocotyledons, and 3 families belong to Gymnosperms each represented by only one species. The results of this study showed that the dominance of the family Asteraceae with 65 species, followed by the family Fabaceae with 48 species, the family Poaceae with 41 species, the family Brassicaceae with 20 species, the family Chenopodiaceae with 17 species, the family Liliaceae with 14 species, and the family Lamiaceae with 13 species. Other families are represented by 7 species or less. The present results have also shown that the dominance of the genera Plantago with 9 species, followed by Ononis and Astragalus with 7 species each. Analysis of lifeform spectrum have indicated that the predominance of therophytes with 218 species, followed by Hemicryptophytes with 61 species. However, chorotype spectrum analysis have shown that the dominance of Mediterranian with 164 species, followed by Mediterrean/ Iranu-Turanean with 80 species.